(untitled) (Baghdad Science Journal, 2009)
Thin films of CdS were deposited on glass substrates using a chemical bath deposition technique from aqueous solutions of Cadmium sulfate (CdS) and thiouria. The films grown from the bath are uniform and adherent, have a high transmittance in the visible region. The CdS films properties studied include optical transmission, optical constant, dielectric constant, optical conductivity, and band gaps. The films in this study produced fairly high transmission (> 86% between 500 and 900). Band gaps of (2.4 eV) for direct transition were obtained. Such films could be used as photocells and other photoconductive devices, thin film transistors and diodes, piezoelectric ultrasonic transducers and amplifiers, piezoelectric acoustic resonators and electron beam-pumped lasers.